EFECTO DE TRES DILUTORES EN LA CONSERVACIÓN DEL SEMEN DE ALPACAS - Huanca L., Wilfredo (2012)
The present workwas carried out at the Experimental Research Station Quimsachata- INIA, Puno. The objective was to evaluate the efficiency of three semen extenders in alpaca semen: Tris-glucose,Tris-fructose and a pig´s commercial extender. Twelve animals were selected for semen collection using the artificial vagina. Males were trained for a month.Mean values for semen parameterswere: volume of 2.7 ± 0.8ml, viscosityof 1. 04 ± 0.3, motility of 54.0 ± 8.0%, pHtowards to alkaline, concentration of 248,000 sperms/ml, and themost common color wasmilkywhite. The average time for the copula was 26.5 ± 3.8 minutes. Semen was diluted in 1:2 and the dilutions were evaluated on individual motility as the only parameter for sperm viability. The extender Tris-glucose had an average of 5.8 ± 1.1 hours viability, Tris-fructose had 6.1 ± 2.5 hours, and the commercial extender had 5.5 ± 1.0 hours, without statistical differences between extenders.